Composite silver soldering paste and preparation method and application thereof

By secondary growth on the basis of nano silver particles, the multi-scale composite silver solder paste is solved, and the shrinkage crack problem and high production cost of nano silver solder paste are achieved, and high performance and low cost solder joints are achieved.

CN119489294APending Publication Date: 2025-02-21合肥钧联汽车电子有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411936009.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-02-21

Smart Images

  • Figure CN119489294A_ABST
    Figure CN119489294A_ABST
Patent Text Reader

Abstract

The invention provides composite silver soldering paste and a preparation method and application thereof.The preparation method comprises the following steps that silver nitrate and PVP are dissolved in an ethylene glycol solution, and stirring is conducted for 20-45 min through a constant-temperature magnetic stirrer at the temperature of 45-75 DEG C; adding a certain amount of HCl into the mixed solution, magnetically stirring for 15-30 minutes, and cooling to room temperature; putting the mixture into a reaction kettle, and performing vacuum constant-temperature heating for 150-200min at 100-190 DEG C; and after washing with deionized water and absolute ethyl alcohol, carrying out ultrasonic treatment to obtain the composite silver soldering paste. According to the multi-scale composite silver soldering paste, an ethylene glycol reduction method is adopted, silver ions in a solution are reduced into silver atoms, submicron or micron particles are secondarily grown on the basis of nano-silver particles, and the multi-scale composite silver soldering paste is prepared and has better electrical and mechanical properties; the multi-scale silver particles are easy to generate, the reaction conditions are easy to control, the preparation method is simple, safe and environmentally friendly, the needed raw material types are few, the number of devices is small, few organic matter is added, and the nano-silver particles controllable in morphology and size are easy to obtain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electronic packaging materials, and in particular relates to a composite silver solder paste and a preparation method and application thereof. Background Art

[0002] Due to the superior electrical and thermal conductivity of silver, the research on silver sintering technology has received extensive attention. Many studies have confirmed that the application of silver paste and substrate to achieve low-temperature interconnection benefits from the nano-size effect and pressure-assisted effect. The use of pure nano silver paste can reduce the sintering temperature to below 200°C, but the material cost is 10 times that of micron silver paste. It is more advantageous to use small-sized silver particles for sintering. The silver paste prepared with silver nanoparticles of 100nm in size forms a copper / silver paste / copper interconnection structure. After being kept at 300°C for 5min, the shear strength of the sintered joint obtained is less than 10MPa. Under the same sintering conditions, the silver paste prepared with 11nm silver nanoparticles obtains a sintered joint with a shear strength of up to 40MPa. At present, existing research has been able to achieve low-temperature, low-pressure or pressureless sintering by improving the size of nanoparticles, the surface coating of particles, and the composition of solder paste. However, the spatial stacking density of single-sized nano silver is low, and shrinkage cracks will occur due to volume shrinkage during sintering, reducing the reliability of sintered solder joints; and the high production cost of nano silver particles makes the application of pure nano silver paste have certain problems. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a method of reducing silver ions in a solution into silver atoms by using ethylene glycol reduction, and secondarily growing submicron or micron particles on the basis of nanosilver particles to prepare a multi-scale composite silver solder paste, which can provide a dense sintered joint by sintering.

[0004] The first aspect of the present application provides a method for preparing a composite silver solder paste, comprising the following steps:

[0005] 1) Dissolve silver nitrate and PVP in ethylene glycol solution, stir at 45-75°C in a constant temperature magnetic stirrer for 20-45 minutes to obtain a colorless and transparent mixed solution;

[0006] 2) Add a certain amount of HCl to the mixed solution, stir magnetically for 15 to 30 minutes, and when the synthesis is complete, cool the product to room temperature;

[0007] 3) The cooled product is placed in a reactor and heated at 100-190°C in vacuum for 150-200 minutes;

[0008] 4) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and after ultrasonic vibration, a multi-size composite silver solder paste with uniformly dispersed silver particles is obtained.

[0009] In any embodiment, in step 1), the addition ratio of ethylene glycol, silver nitrate and PVP is 100 ml: 1-2 g: 1 g.

[0010] In any embodiment, in step 2), 18 to 25 uL of hydrochloric acid having a concentration of 0.0706 mol / L is added to 100 ml of ethylene glycol.

[0011] In any embodiment, the mass fraction of PVP in the mixed solution of step 1) is 0.53% to 1.06%.

[0012] In any embodiment, the size of the nanosilver particles formed in step 1) is in the range of 50 to 100 nm, and the average diameter of the multi-sized silver particles formed in step 3) is 1 μm±100 nm.

[0013] The second aspect of the present application also provides a composite silver solder paste, which is obtained by the above-mentioned preparation method.

[0014] The third aspect of the present application also provides an application of a composite silver solder paste. The silver solder paste prepared by the above-mentioned preparation method of the composite silver solder paste is printed on a sintered AMB substrate, and then chip mounting is performed to obtain solder joints of a sandwich structure of chip-silver solder paste-silver-plated copper substrate, and the solder joints are placed in a sintering device for sintering.

[0015] In any embodiment, the silver solder paste is sintered at a sintering temperature of 150° C. to 250° C., a sintering time of 3 min to 5 min, and a sintering pressure of 15 MPa to 20 MPa.

[0016] In any embodiment, the pre-pressing pressure of the sintering pressure is 5 MPa, the pre-pressing time is 2 s, the nitrogen flow rate is 15 to 20 L / min, and the pressurization rate is 2 to 5 MPa / s.

[0017] The beneficial effects of the present invention are as follows: the present application adopts the ethylene glycol reduction method to reduce the silver ions in the solution into silver atoms, and secondary grows submicron or micron particles on the basis of nanosilver particles to prepare a multi-scale composite silver solder paste, and sintering with the composite silver solder paste can provide a dense sintered joint: the composite silver solder paste formed by mixing nanosilver and micron silver can obtain better electrical and mechanical properties than pure nanosilver solder paste, so that small particles can fill the gaps between large particles, so that the porosity of the sintered network is lower, thereby obtaining a sintered joint with excellent performance.

[0018] The multi-scale silver particles of the present application are easy to generate, the reaction conditions are easy to control, the amount of equipment used is small, and the morphology is stably controlled; the product not only maintains the excellent bonding ability of the nano silver solder paste, but also reduces the cost as much as possible; the preparation method of the application scheme is simple, safe, and environmentally friendly, requires a small number of raw materials, and a small amount of organic solvent is added, and it is easy to obtain nano silver particles with controllable morphology and size. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of the composite silver solder paste obtained by the preparation method of the composite silver solder paste of the present application;

[0020] Figure 2 This is a morphological diagram of the primary growth of nano silver particles in the preparation method of the composite silver solder paste of the present application;

[0021] Figure 3 is a morphology diagram of the nanosilver particles in Comparative Example 1;

[0022] Figure 4 is a morphology diagram of the nanosilver particles in Comparative Example 2;

[0023] Figure 5 This is a SEM image of the morphology of nanosilver after secondary growth in the preparation method of the composite silver solder paste of the present application;

[0024] Figure 6 This is the SEM image of the nanosilver morphology after secondary growth in Comparative Example 3;

[0025] Figure 7 This is the SEM image of the nanosilver morphology after secondary growth in Comparative Example 4;

[0026] Figure 8 This is a scanning electron microscope image of the composite silver solder paste obtained in Comparative Example 5. DETAILED DESCRIPTION

[0027] Hereinafter, the composite silver solder paste of the present application, its preparation method and application implementation methods are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0028] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0029] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0031] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0032] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0033] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0034] In one embodiment of the present application, the present application proposes a method for preparing a composite silver solder paste, comprising the following steps:

[0035] 1) Dissolve silver nitrate and PVP in ethylene glycol solution, stir at 45-75°C in a constant temperature magnetic stirrer for 20-45 minutes to obtain a colorless and transparent mixed solution;

[0036] The present application directly dissolves silver nitrate and PVP in an ethylene glycol solution, thereby increasing the reaction speed and making the mixing of silver nitrate and PVP more uniform; the production operation is also more convenient, thereby improving production efficiency.

[0037] At 45-75°C, the silver source can be better dissolved in ethylene glycol to prepare the silver source solution. If the temperature is too low, the silver ions in the silver source solution will be unevenly distributed. If the temperature is too high, ethylene glycol will act as a reducing agent to reduce the silver particles prematurely.

[0038] 2) Add a certain amount of HCl to the mixed solution, stir magnetically for 15 to 30 minutes, and when the synthesis is complete, cool the product to room temperature;

[0039] Cool to room temperature to form a stable AgCl colloidal solution, and avoid excessively high temperature, which will lead to increased attraction between colloidal particles, thereby increasing agglomeration and sedimentation, and affecting the precipitation of silver ions in the colloid.

[0040] 3) The cooled product is placed in a reactor and heated at 100-190°C in vacuum for 150-200 minutes;

[0041] When the temperature is too low, there are very few composite particles with secondary growth of silver particles. As the temperature rises, the number of particles with secondary growth increases. The optimal reaction temperature is 150-190°C, which can form a more ideal composite silver particle size. Silver particles reacting at 160°C can show a large number of secondary growth.

[0042] 4) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and after ultrasonic vibration, a multi-size composite silver solder paste with uniformly dispersed silver particles is obtained.

[0043] Step 3) Raise the reaction temperature to increase the driving energy for interconnection. Ethylene glycol decomposes into ethanolaldehyde under heating conditions, and undergoes redox reaction with the remaining unreacted AgNO3 and the generated AgCl to convert Ag+ Converted to Ag, reaction equation:

[0044] HOCH2CHO+2Ag + +H2O→HOCH2COOH+2Ag+2H +

[0045] Ag + It is transformed into Ag of different sizes and shapes, and after the Ostwald Ripening process, the generated nanoparticles gradually deposit on the micron particles and crystallize to form new micron particles. After the nanosilver is heated at 100-190°C for a certain period of time, the micron silver undergoes the Ostwald Ripening process, and the generated nanoparticles gradually deposit on the micron particles and crystallize to form new micron particles. At the same time, AgCl is decomposed, and nanosilver particles with smaller particle size are precipitated, forming an organic whole on the surface. After heating for a certain period of time, the particles finally form secondary growth particles.

[0046] When the temperature is too low, the nanosilver particles rarely show the phenomenon of secondary growth particles, and the dark areas after electron beam irradiation change significantly; the nanosilver particles reacted at 160-190°C basically show the phenomenon of secondary growth particles, and the dark areas after electron beam irradiation change very little, and the morphology tends to be stable.

[0047] The colloidal solution contains both AgCl and Ag. If the heating time is insufficient, a large amount of AgCl is not decomposed, that is, silver particles with smaller particle sizes are not precipitated.

[0048] In some embodiments, the addition ratio of ethylene glycol, silver nitrate and PVP in step 1) is 100 ml: 1-2 g: 1 g. The amount of PVP is 50% to 100% (mass fraction) of silver nitrate. Under this ratio, ultrafine silver particles with high sphericity and good dispersion performance can be prepared. Ethylene glycol is used as both a reducing agent and a solvent in the preparation of silver particles. The amount added needs to be sufficient to dissolve PVP and provide sufficient reducing power to reduce silver nitrate.

[0049] The amount of PVP added will affect the morphology of silver particles, changing them from dendritic to spherical, and improving the dispersion performance; PVP is used as a dispersant, and its amount will affect the dispersion performance of silver particles. An appropriate amount of PVP can improve the dispersion of silver particles; when the amount of PVP is 50% to 100% (mass fraction) of silver nitrate, spherical silver powder with a smooth surface and good dispersion can be prepared. Within this mass fraction range, the amount of PVP added has a significant effect on the morphology and dispersibility of silver powder.

[0050] The concentrations of silver nitrate and PVP need to be moderate. When the silver nitrate concentration is higher than the PVP concentration during crystal growth, the number of Ag atoms reduced from silver nitrate continues to increase. When the PVP coating of these Ag atoms is not thorough, the Ag deposition will be too coarse, resulting in excessive size. When the silver nitrate concentration is too low, the number of reduced Ag atoms will be too small, the deposition will be incomplete, and there will be fewer large silver particles.

[0051] In some embodiments, in step 2), 18 to 25 uL of hydrochloric acid having a concentration of 0.0706 mol / L is added to 100 ml of ethylene glycol.

[0052] That is, 1.2g of silver nitrate is dissolved in 100ml of ethylene glycol solution, and the silver ion concentration is 0.0706mol / L. The chloride ion concentration is controlled to be equal to the silver ion concentration to form a colloidal solution, and the chloride ion concentration is 0.0706mol / L. The added volume range is 18~25uL. The molar number of chloride ions in hydrochloric acid is 1.2708×10 -6 mol~1.9768×10 -6 mol. Hydrochloric acid can be used with a mass fraction of 38%.

[0053] The chloride ion concentration in hydrochloric acid affects the shape of silver particles. If the chloride ion concentration is too low, there will be more linear silver particles and rod-shaped silver particles. Increasing the chloride ion concentration can adjust the shape of silver particles to polyhedral particles. However, if the chloride ion concentration is too high, it will also affect the subsequent precipitation of silver ions.

[0054] Controlling the amount of hydrochloric acid added can ensure that the obtained nanosilver particles have a uniform morphology and avoid the appearance of rod-shaped nanosilver or polyhedral nanosilver and a mixture thereof.

[0055] A colloidal solution containing AgCl is formed at room temperature, and then the reaction bottle is moved to a magnetic stirrer for stirring. The synthesis is completed and the product is cooled to room temperature. Before the addition of hydrochloric acid, the solution is transparent and almost light yellow. After the addition, a white precipitate is formed, forming a turbid white mixture.

[0056] AgCl provides halide ions, acts as a capping agent on the (100) surface of the formed particles, and can also control the Ag + The reversibility of the thermodynamic reaction between Ag and Ag, that is, in the subsequent heating process, the peroxide of the AgCl reduction reaction is stimulated into small silver particles and adsorbed on the surface of the large particles; the Cl in the reaction system - If the content is too little or too much, particles of various shapes will appear in the final product. - The role played is mainly to reduce the presence of free silver cations in the solution by combining with silver ions to form AgCl structure, prevent the accumulation of silver cations and seed crystals, and ensure the gradual release of silver cations in the subsequent growth stage.

[0057] In the process of particle formation, the (100) face acts as a capping agent, which means that during particle growth, certain substances (such as PVP or other ligands) will preferentially adsorb on the (100) face, thereby affecting the growth rate and morphology of the crystal. This selective adsorption can lead to the inhibition of crystal growth in certain directions, while the growth in other directions is relatively faster, ultimately forming particles of a specific morphology. For example, in the synthesis of silver nanostructures, the preferential binding of PVP to the Ag (100) face can lead to the formation of silver nanocubes.

[0058] (100) plane refers to the crystal plane index in crystallography, which indicates a specific plane composed of atoms, ions or molecules in the crystal. A specific capping agent preferentially adsorbs on a specific crystal plane, and the crystal grows along this direction, thereby controlling the morphology of the crystal. A way to describe the orientation of a crystal plane in a crystal, usually expressed as (hkl), where h, k, and l are three integers that represent the reciprocals of the relative intercepts of the crystal plane and the three crystal axes of the crystal, and are mutually prime.

[0059] In some embodiments, the mass fraction of PVP in the mixed solution of step 1) is 0.53% to 1.06%.

[0060] By controlling the dosage of PVP, the morphology of silver particles changes from dendritic to spherical, and the dispersion performance becomes better; PVP is used as a dispersant, and its addition amount will affect the dispersion performance of silver particles. An appropriate amount of PVP can improve the dispersion of silver particles and prepare spherical silver powder with a smooth surface and good dispersion. Within this mass fraction range, the addition amount of PVP has a significant effect on the morphology and dispersibility of silver powder.

[0061] In some embodiments, the size of the nanosilver particles formed in step 1) is in the range of 50 to 100 nm, and the average diameter of the multi-scale silver particles formed in step 3) is 1 μm ± 100 nm, preferably 1 μm ± 50 nm.

[0062] Small particles grow autonomously on a 1-micron scale, and micron-sized particles with an average diameter of 1 micron are highly compatible with nano-sized particles. Silver particles within 100 nm are considered excellent nano-sized particles.

[0063] The second aspect of the present application also provides an application of a composite silver solder paste. The silver solder paste prepared by the above-mentioned preparation method of the composite silver solder paste is printed on a sintered AMB substrate, and then the chip is mounted to obtain solder joints of a sandwich structure of chip-silver solder paste-silver-plated copper substrate, and the solder joints are placed in a sintering device for sintering.

[0064] Silver sintering is performed on the AMB substrate to form effective interconnection between metal and non-metal.

[0065] In some embodiments, the silver solder paste is sintered at a temperature of 150 to 250° C., a sintering time of 3 to 5 minutes, and a sintering pressure of 15 MPa to 20 MPa.

[0066] The pre-pressing pressure of the sintering pressure is 5 MPa, the pre-pressing time is 2 s, the nitrogen flow rate is 15-20 L / min, and the pressurization rate is 2-5 MPa / s.

[0067] By pre-pressing and applying pressure, the silver solder paste is evenly distributed and dense, improving the quality of sintering. Nitrogen plays multiple roles in silver sintering, such as protecting the furnace lining, maintaining the atmosphere in the furnace, promoting the sintering process, improving product quality, and reducing the impact of oxygen. These roles jointly ensure the smooth progress of the sintering process and the steady improvement of product quality.

[0068] Preparation of silver particles - printing of silver solder paste (printing the composite silver solder paste on the sintered AMB substrate) - chip mounting (and then chip mounting) - sintering (to obtain a solder joint of a sandwich structure of chip-silver solder paste-silver-plated copper substrate, the solder joint is placed in a sintering device for sintering at a sintering temperature of 150-250°C for 3-5 minutes). The solder joint sintering temperature can be greater than 150°C and less than 180°C.

[0069] Example

[0070] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0071] Example 1

[0072] A method for preparing a composite silver solder paste comprises the following steps:

[0073] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0074] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0075] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0076] 4) Take 18uL of hydrochloric acid with a concentration of 0.0706mol / L and add it to the mixed solution to form a colloidal solution containing AgCl at room temperature. Then move the reaction bottle to a magnetic stirrer and stir for 20 minutes. The synthesis is completed and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent and almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0077] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 160°C for 180 min.

[0078] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0079] 7) Silver sintering is performed on the AMB substrate. The sintering temperature of the silver solder paste is 150°C and the sintering time is 5 minutes. This verifies the effective interconnection between the metal and the non-metal. The temperature resistance, shear strength, and temperature level required for sintering of the sintered joint are measured to verify the reliability of the multi-sized silver particles.

[0080] Example 2

[0081] A method for preparing a composite silver solder paste comprises the following steps:

[0082] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0083] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 0.6 g of PVP, and dissolve them in the ethylene glycol solution.

[0084] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0085] 4) Take 0.0706mol / L hydrochloric acid, add 20uL of volume to the mixed solution, form a colloidal solution containing AgCl at room temperature, then move the reaction bottle to a magnetic stirrer and stir for 20min, the synthesis is complete, and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent, almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0086] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 160°C for 180 min.

[0087] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0088] 7) Silver sintering is performed on the AMB substrate. The sintering temperature of the silver solder paste is 150°C and the sintering time is 5 minutes. This verifies the effective interconnection between the metal and the non-metal. The temperature resistance, shear strength, and temperature level required for sintering of the sintered joint are measured to verify the reliability of the multi-sized silver particles.

[0089] Example 3

[0090] A method for preparing a composite silver solder paste comprises the following steps:

[0091] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0092] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0093] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0094] 4) Take 0.0706mol / L hydrochloric acid, add 20uL of volume to the mixed solution, form a colloidal solution containing AgCl at room temperature, then move the reaction bottle to a magnetic stirrer and stir for 20min, the synthesis is complete, and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent, almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0095] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 180°C for 180 min.

[0096] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0097] 7) Silver sintering is performed on the AMB substrate. The sintering temperature of the silver solder paste is 150°C and the sintering time is 5 minutes. There is an effective interconnection between the metal and the non-metal. The temperature resistance, shear strength, and temperature level required for sintering of the sintered joint are measured to verify the reliability of multi-sized silver particles.

[0098] Example 4

[0099] A method for preparing a composite silver solder paste comprises the following steps:

[0100] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0101] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0102] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0103] 4) Take 0.0706mol / L hydrochloric acid, add 20uL of volume to the mixed solution, form a colloidal solution containing AgCl at room temperature, then move the reaction bottle to a magnetic stirrer and stir for 20min, the synthesis is complete, and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent, almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0104] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 160°C for 180 min.

[0105] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0106] 7) Silver sintering is performed on the AMB substrate. The sintering temperature of the silver solder paste is 150°C and the sintering time is 5 minutes. This verifies the effective interconnection between the metal and the non-metal. The temperature resistance, shear strength, and temperature level required for sintering of the sintered joint are measured to verify the reliability of the multi-sized silver particles.

[0107] Comparative Example 1

[0108] A method for preparing a composite silver paste comprises the following steps:

[0109] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0110] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0111] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0112] 4) Take 7uL of hydrochloric acid with a concentration of 0.0706mol / L and add it to the mixed solution to form a colloidal solution containing AgCl at room temperature. Then move the reaction bottle to a magnetic stirrer and stir for 20 minutes. The synthesis is completed and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent and almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0113] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 160°C for 180 min.

[0114] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0115] Comparative Example 2

[0116] A method for preparing a composite silver paste comprises the following steps:

[0117] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0118] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0119] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0120] 4) Take 15uL of hydrochloric acid with a concentration of 0.0706mol / L and add it to the mixed solution to form a colloidal solution containing AgCl at room temperature. Then move the reaction bottle to a magnetic stirrer and stir for 20 minutes. The synthesis is completed and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent and almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0121] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 160°C for 180 min.

[0122] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0123] Comparative Example 3

[0124] A method for preparing a composite silver paste comprises the following steps:

[0125] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0126] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0127] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0128] 4) Take 0.0706mol / L hydrochloric acid, add 20uL of volume to the mixed solution, form a colloidal solution containing AgCl at room temperature, then move the reaction bottle to a magnetic stirrer and stir for 20min, the synthesis is complete, and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent, almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0129] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 100°C for 180 min.

[0130] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0131] Comparative Example 4

[0132] A method for preparing a composite silver paste comprises the following steps:

[0133] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0134] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0135] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0136] 4) Take 0.0706mol / L hydrochloric acid, add 20uL of volume to the mixed solution, form a colloidal solution containing AgCl at room temperature, then move the reaction bottle to a magnetic stirrer and stir for 20min, the synthesis is complete, and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent, almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0137] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 130°C for 180 min.

[0138] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0139] Comparative Example 5

[0140] A method for preparing a composite silver paste comprises the following steps:

[0141] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0142] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0143] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0144] 4) Take 0.0706mol / L hydrochloric acid, add 20uL of volume to the mixed solution, form a colloidal solution containing AgCl at room temperature, then move the reaction bottle to a magnetic stirrer and stir for 20min, the synthesis is complete, and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent, almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0145] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 160°C for 60 min.

[0146] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0147] Comparative Example 6

[0148] A multi-size composite nano silver paste is prepared by the following steps:

[0149] (1) Silver nitrate and PVP are dissolved in ethylene glycol at room temperature to obtain solutions A and B, respectively. Solution A is added dropwise to solution B which is stirred at high speed, and then heated to 150°C for reaction for 1 hour. The mass fraction of silver nitrate in solution A is 4wt%, the mass fraction of PVP in solution B is 2wt%, and the mass ratio of solution A to solution B is 1:1. After the reaction is completed, acetone is added for flocculation and centrifugation. After the supernatant is discarded, ethanol is added for washing and centrifugation, and the process is repeated 3 times to obtain small-sized nanosilver seed crystals with a size distribution of 80-150nm.

[0150] (2) Ultrasonic dispersion of small-sized nanosilver seed crystals into ethylene glycol solution at a mass ratio of 10 wt%, dropwise addition of newly prepared solution A, and heating to 150° C. for reaction for 1 h. After the reaction, acetone was added for flocculation and centrifugation, and the supernatant was discarded and ethanol was added for washing and centrifugation, which was repeated 3 times to obtain multi-sized composite nanosilver particles of 200-500 nm.

[0151] (3) The multi-sized composite nanosilver particles are uniformly mixed with ethylene glycol to obtain a silver paste preparation, and then the silver paste preparation is heated to 80° C. in a water bath to remove excess solvent, and then mechanically stirred to obtain a multi-sized composite nanosilver paste.

[0152] Comparative Example 7

[0153] A multi-size composite nano silver paste is prepared by the following steps:

[0154] (1) Heat a constant temperature magnetic stirrer to 60°C, take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, dissolve them in the ethylene glycol solution, stir for 30 min in the constant temperature magnetic stirrer, and obtain a colorless transparent solution.

[0155] (2) placing the stirred solution into a reaction kettle, placing it into a vacuum constant temperature drying oven, and heating it at 160° C. for 180 min; washing it with deionized water and anhydrous ethanol, centrifuging it to obtain secondary growth silver particles, and subjecting it to ultrasonic vibration to make the silver particles evenly dispersed.

[0156] The relevant parameters of the welding points of the above-mentioned embodiments 1 to 12 and comparative examples 1 to 7 are shown in the following Table 1.

[0157] Comparative Example 8

[0158] A method for preparing a composite silver solder paste comprises the following steps:

[0159] 1) Heat the constant temperature magnetic stirrer to 60°C;

[0160] 2) Take 100 ml of ethylene glycol solution as solvent, weigh 1.2 g of silver nitrate and 1.2 g of PVP, and dissolve them in the ethylene glycol solution.

[0161] 3) Place the mixture in the above-mentioned constant temperature magnetic stirrer and stir for 30 minutes to obtain a colorless transparent solution.

[0162] 4) Take 0.0706mol / L hydrochloric acid, add 20uL of volume to the mixed solution, form a colloidal solution containing AgCl at room temperature, then move the reaction bottle to a magnetic stirrer and stir for 20min, the synthesis is complete, and the product is cooled to room temperature. Before adding hydrochloric acid, the solution is transparent, almost light yellow. After adding, a white precipitate is formed, forming a turbid white mixture;

[0163] 5) The stirred solution was placed in a reaction kettle, placed in a vacuum constant temperature drying oven, and heated at 160°C for 180 min.

[0164] 6) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and the silver particles are evenly dispersed by ultrasonic vibration.

[0165] 7) Silver sintering is performed on the AMB substrate. The sintering temperature of the silver solder paste is 100°C and the sintering time is 5 minutes. This verifies the effective interconnection between the metal and the non-metal. The temperature resistance, shear strength, and temperature level required for sintering of the sintered joint are measured to verify the reliability of the multi-sized silver particles.

[0166] Table 1: Performance test results of Examples 1 to 4 and Comparative Examples 1 to 7

[0167]

[0168]

[0169] According to the above results, it can be seen that Examples 1, 2, 3 and 4 can all prepare particles close to the target size and achieve good performance. The silver solder paste prepared by the silver particles has excellent sintering performance.

[0170] In contrast, in Comparative Examples 1, 2, and 3, the conditions were not within the appropriate experimental range, and the prepared silver particles did not achieve effective improvement in performance. Comparative Example 8 and Example 4 illustrate that the same composite silver paste has different performance differences when used at different sintering temperatures.

[0171] The porosity of sintered silver paste has a significant effect on the macroscopic mechanical properties of the material. A decrease in porosity usually leads to an increase in the elastic modulus and yield strength of the sintered silver material. However, this does not mean that the lower the porosity, the better. In the final stage of plastic deformation, as the strain increases, the stress of the material shows a significant downward trend, making the material more susceptible to damage. In addition, the change in porosity has a significant effect on the shear deformation of sintered silver nanoparticles. An increase in porosity leads to an increased probability of crack initiation and propagation in porous areas, which may lead to a decrease in shear strength.

[0172] Therefore, although lower porosity can improve certain mechanical properties of sintered silver materials, too low a porosity may cause the material to be more easily damaged during the plastic deformation stage and may have a negative impact on shear performance. The present application controls the porosity to achieve the best comprehensive performance of the welding point.

[0173] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a composite silver solder paste, characterized in that: The following steps are involved: 1) Dissolve silver nitrate and PVP in ethylene glycol solution, stir at 45-75°C in a constant temperature magnetic stirrer for 20-45 minutes to obtain a colorless and transparent mixed solution; 2) Add a certain amount of HCl to the mixed solution, stir magnetically for 15 to 30 minutes, and when the synthesis is complete, cool the product to room temperature; 3) The cooled product is placed in a reactor and heated at 100-190°C in vacuum for 150-200 minutes; 4) After washing with deionized water and anhydrous ethanol, the secondary grown silver particles are obtained by centrifugal separation, and after ultrasonic vibration, a multi-size composite silver solder paste with uniformly dispersed silver particles is obtained.

2. The preparation method according to claim 1, characterized in that: In the step 1), the addition ratio of ethylene glycol, silver nitrate and PVP is 100 ml: 1-2 g: 1 g.

3. The preparation method according to claim 1, characterized in that: In the step 2), 18 to 25 uL of hydrochloric acid with a concentration of 0.0706 mol / L is added to 100 ml of ethylene glycol.

4. The preparation method according to claim 1, characterized in that: The mass fraction of PVP in the mixed solution of step 1) is 0.53% to 1.06%.

5. The preparation method according to claim 1, characterized in that: The size range of the nano silver particles formed in step 1) is 50-100 nm, and the average diameter of the multi-scale silver particles formed in step 3) is 1 μm±100 nm.

6. A composite silver solder paste, characterized in that: The preparation method is as described in any one of claims 1 to 5.

7. An application of a composite silver solder paste, wherein the silver solder paste prepared by the preparation method of the composite silver solder paste as described in any one of claims 1 to 5 is printed on a sintered AMB substrate, and then chip bonding is performed to obtain solder joints of a sandwich structure of chip-silver solder paste-silver-plated copper substrate, and the solder joints are placed in a sintering device for sintering.

8. The use according to claim 7, characterized in that: The silver solder paste is sintered at a sintering temperature of 150° C. to 250° C., a sintering time of 3 min to 5 min, and a sintering pressure of 15 MPa to 20 MPa.

9. The use according to claim 8, characterized in that: The pre-pressing pressure of the sintering pressure is 5 MPa, the pre-pressing time is 2 s, the nitrogen flow rate is 15-20 L / min, and the pressurization rate is 2-5 MPa / s.